Breast Cancer 2013 – Interpretation of New and Known Data - Lux, M. P.; Maass, N.; Schütz, F.; Schwidde, I.; Fasching, P. A.; Fehm, T.; Janni, W.; Kümmel, S.; Kolberg, H.-C.; Lüftner, D. (Geburtshilfe und Frauenheilkunde, 2013)
The treatment options and characteristics for therapeutic decisions for patients with primary and advanced breast cancer are becoming more and more numerous. New targeted therapies in combination with established chemotherapy regimens are expending the spectrum but potentially promising combinations do not also give a better result. The latest data from pharmacogenomics point to prognosis and predictive factors that take not only the properties of the tumour but also the hereditary genetic features of the patient into account. Current therapy decisions are thus based on a combination of classical clinical and modern molecular biomarkers. Health-economic aspects are also being taken into account more often, so that health-political considerations may also play a part. The present review article summarises parts of the results presented at the 2012 San Antonio Breast Cancer Symposia (SABCS), ESMO 2012 and St. Gallen 2013 together with new and important publications on the prevention of and therapy for breast cancer.
Keywords: breast cancer; treatment; local recurrence; metastases; trials